Musculoskeletal disorders and psychosocial factors at work - Roquelaure, Yves (Brussels, 2018)
"This report presents the current state of scientific knowledge on the ways in which psychosocial factors influence musculoskelatal disorders (MSDs), and their impact on work capacity and quality. Almost 40m workers in Europe suffer from MSDs of the limbs and back and are the most common occupational disease in the EU. The aim of the paper is influence intervention efforts and provide scientifically-grounded recommendations to improve the health of Europe’s workers."